A Pilot Study of Laparoscopic Doppler Ultrasound Probe to Map Arterial Vascular Flow within the Neurovascular Bundle during Robot-Assisted Radical Prostatectomy - Ketan K. Badani; Edan Y. Shapiro; William T. Berg; Sarah Kaufman; Ari Bergman; Chris Wambi; Arindam RoyChoudhury; Trushar Patel (Prostate Cancer)
Purpose. To report on the feasibility of a new Laparoscopic Doppler ultrasound (LDU) technology to aid in identifying and preserving arterial blood flow within the neurovascular bundle (NVB) during robotic prostatectomy (RARP). Materials and Methods. Nine patients with normal preoperative potency and scheduled for a bilateral nerve-sparing procedure were prospectively enrolled. LDU was used to measure arterial flow at 6 anatomic locations alongside the prostate, and signal intensity was evaluated by 4 independent reviewers. Measurements were made before and after NVB dissection. Modifications in nerve-sparing procedure due to LDU use were recorded. Postoperative erectile function was assessed. Fleiss Kappa statistic was used to evaluate inter-rater agreement for each of the 12 measurements. Results. Analysis of Doppler signal intensity showed maintenance of flow in 80% of points assessed, a decrease in 16%, and an increase in 4%. Plane of NVB dissection was altered in 5 patients (56%) on the left and in 4 patients (44%) on the right. There was good inter-rater reliability for the 4 reviewers. Use of the probe did not significantly increase operative time or result in any complications. Seven (78%) patients had recovery of erections at time of the 8-month follow-up visit. Conclusions. LDU is a safe, easy to use, and effective method to identify local vasculature and anatomic landmarks during RARP, and can potentially be used to achieve greater nerve preservation.